The sensitivity of multiple ecotoxicological assays for evaluating Microcystis aeruginosa cellular algal organic matter and contribution of cyanotoxins to the toxicity - Šrédlová, Kamila; Šilhavecká, Simona; Linhartová, Lucie; Semerád, Jaroslav; Michalíková, Klára; Pivokonský, Martin; Cajthaml, Tomáš (Toxicon, 2021)
Secondary metabolites of cyanobacteria and algae released during algal blooms often exhibit toxic effects, but only a small number of the metabolites are the subject of routine analytical screenings. Alternatively, ecotoxicological assays offer a better representation of the overall negative effects. The aim of this work was to compare multiple assays in their sensitivity towards cellular algal organic matter (COM) of the toxin-producing cyanobacterium Microcystis aeruginosa. Multiple endpoints were investigated: mortality, growth inhibition, bioluminescence inhibition, genotoxicity, endocrine-disrupting effects, oxidative stress, and the induction of ethoxyresorufin-O-deethylase (EROD). Three rainbow trout (Oncorhynchus mykiss) cell lines as well as representatives of bacteria, yeasts, algae, vascular plants, and crustaceans were employed, and the results were expressed per mg of dissolved organic carbon (DOC) in the COM. M. aeruginosa COM was toxic to the RTgill-W1, RTG-2, and RTL-W1 cell lines (EC50 values ranging from 0.48 ± 0.02 to 1.9 ± 0.1 mgDOC/L), to the crustacean Thamnocephalus platyurus (LC50 = 20 ± 1 mgDOC/L), and to Lepidium sativum (IC50 = 241 ± 13 mgDOC/L). In contrast, no effect was observed for bacteria and yeasts, and the growth of the alga Desmodesmus subspicatus was even stimulated. No genotoxicity, endocrine-disrupting effects or increase in oxidative stress or EROD activity was detected. The content of six microcystins (MC-LR, MC-RR, MC-YR, MC-LY, MC-LW, and MC-LF), anatoxin-a, cylindrospermopsin, and nodularin in the M. aeruginosa COM was determined by liquid chromatography-tandem mass spectrometry. An artificially prepared mixture of the detected cyanotoxins in the corresponding concentrations did not induce response in the O. mykiss cell lines and T. platyurus, suggesting that other cyanobacterial metabolites are responsible for the toxicity of M. aeruginosa.
Keywords: eutrofizace; Cyanobacteria; mikrocystiny; Microcystis aeruginosa; Cellular algal organic matter; sinice; Microcystis; Eutrophication; Harmful algal blooms; Microcystin; Microcystins; Rainbow trout cell lines; Cytotoxicity